Avaliação da eficiência de precipitadores eletrostáticos na coleta de nanopartículas a partir de modificações operacionais e geométricas - Andrade, Raíssa Gabrielle Silva Araújo (2024)
The application of air pollution control systems has become indispensable for industries and environments that have a high amount of particulate matter. Due to the harmful nature associated with the inhalation of these particles, it is necessary to reduce their concentration in the emissions dispersed in the air. Thus, the electrostatic precipitator is a viable alternative, due to its versatile operation and high efficiency, with the performance of this equipment being directly related to the operating conditions used and its geometry. The present work aimed to study the influence of geometric configurations on the efficiency of nanoparticle collection. For this, two electrostatic precipitators, single and double stage, located in research laboratories in Brazil and France, which differ in size and associated experimental unit, were evaluated. Therefore, the present work was divided into chapters, to allow a more detailed analysis of each of the experiments. One chapter presents the study of the single-stage electrostatic precipitator, in which the effects of inlet spacing were evaluated on the electrical characteristics and performance of the electrostatic precipitator in nanoparticle collection. Specifically, the analysis involved the use of 1 and 3 discharge electrodes. Next, the inclusion of a collection net was evaluated, which occurred in conjunction with the use of 1 discharge electrode. For this, an aerosol formed from a 0.1 g/L NaCl solution was used. The experiments were carried out for a particle diameter range between 6.15 and 241.4 nm. The electrostatic precipitator used has two collecting plates 10 cm high and 30 cm long, spaced 6.5 cm apart. 0.4 mm stainless steel wires were used as discharge electrodes, spaced 6.5 cm apart. The results indicated that the electric current values showed little or no variation when comparing the spacings used. In addition, the spacings that achieved the highest collection efficiencies were 15 cm (1 wire), 7.5 and 10.5 cm (3 wires), with the 23 cm configuration being the most favored by the insertion of the collection net. On the other hand, another chapter evaluated the double-stage electrostatic precipitator, composed of an ionizer 7 cm in diameter and 15 cm high, containing 8 discharge electrodes, and a collector with 8 collector plates 7 cm wide and 10 cm high. The experiments were carried out with an aerosol from a 5 g/L NaCl solution and for particles between 10 and 154 nm. This study was conducted in 5 stages, aimed at evaluating the collection efficiency with different voltages of the collector, the ionizer, air velocity, the distance between the ionizer and the collector and the type of ionizer, in addition to evaluating the ozone concentration and electrical charge per particle. The results indicated that the most efficient conditions were those that presented the highest voltages in both the collector and the ionizer. However, under these same conditions, ozone production was significantly high, reaching around 200 ppb. On the other hand, when using lower voltages, with maximum collection efficiencies around 60% and a reduced ozone concentration were obtained. Additionally, it was observed that the increase in the distance between the ionizer and the collector resulted in an increase in collection efficiency, possibly due to the prolongation of the particles residence time. Both the single-stage and double-stage precipitators can present high nanoparticle collection efficiencies, depending on the quantity and positioning of the discharge electrodes (for the single-stage) and the type of ionizer and the spacing between the ionizer and collector (for the double stage), in addition to the operational conditions for both cases. Therefore, it is imperative to thoroughly analyze the results obtained using the electrostatic precipitator, to choose the configuration that most appropriately aligns with the desired conditions.